Improving SoTL Programs: The Impact of a Student Sector - Angela Miller, BS (Park University, 2013)
O' Meara, Terosky, and Neumann (2011) revealed a need to integrate faculty teaching and learning centers with research development programs to further both individual professors' goals of creating innovative pedagogical practices and institutional goals for faculty publication and effective decision making regarding funding allocation. This article suggests that universities implement a scholarship of teaching and learning (SoTL) or teaching-learning enhancement center (TLEC) student sector within these integrated faculty development programs. This will foster more pedagogical ideas and a more democratic institution by giving students a voice in their education while enriching the knowledge of students, faculty, and administrators.